Peran Auditor Internal dalam Pendeteksian dan Pencegahan Fraud Pada Bank Syariah di Kota Bandung - Yogi Ginanjar; E Mulya Syamsul (ITB AAS INDONESIA Surakarta, 2020)
Bareskrim Polri has named two BJB Syariah Bank officials in Bandung City as suspects in a fictitious credit case worth Rp 548 billion. This is one of the big cases that has tarnished Islamic banking, especially in the city of Bandung. The purpose of this research is to conduct a deeper study of the role of internal auditors in detection and prevention of fraud at Islamic Banks in Bandung City. The research method used is descriptive analysis and verification with the type of survey. The independent variable used is the role of the internal auditor. Meanwhile, fraud detection and prevention is used as the dependent variable. The population of this research is all Islamic Banks in Bandung City. The sampling technique used random sampling in order to obtain a sample of 60 Islamic Bank employees in the city of Bandung. The data analysis used was correlation coefficient analysis, determination and hypothesis testing. The role of the Internal Auditor affects Fraud Detection by 26.72%. Meanwhile, the role of the Internal Auditor has an effect on Fraud Prevention by 43.16%.